Study of mast Cells in Appendectomy Specimen - Upadhyay, Janaki V; Shah, Shaila N (Annals of Pathology and Laboratory Medicine, 2020)
Background: Mast cells play an important role in various inflammatory and immune reaction. Mast cells are constantly present in the appendices, and appendix remains one of the common surgical specimens received at pathology laboratory. Mast cells could be one of the important cell population responsible for nerve proliferation and hypertrophy in cases with clinically and histopathologically diagnosed appendicitis. Material and methods: The study was done on 100 surgically resected specimens of appendix received for routine histopathological evaluation at the Department of Pathology, Government Medical College, Bhavnagar, between June 2018 and May 2019. All appendices surgically resected as a therapeutic measure for clinically suspected appendicitis included. Cases of normal appendix and acute gangrenous appendicitis were excluded from the study. The appendices were assessed for their histological changes and density of mast cell infiltration. The mast cells were counted in 1% toluidine blue stained sections. Results: Out of 100 cases of surgically resected appendices, chronic appendicitis was found in 65% of cases and occurred frequently during the second and third decades of life. Highest mast cell count was seen in acute eosinophilic appendicitis and chronic appendicitis. No significant difference was observed in the mean mast cell counts among the different layers of the appendices studied. Conclusion: Mast cell counts were found to be highest in acute eosinophilic appendicitis and chronic appendicitis. Intermediate mast cell counts were seen in acute appendicitis and acute suppurative appendicitis. Mast cells appear to play roles in accentuation of inflammatory process and fibrosis.